Value Co-Creation, Goods and Service Tax (GST) Impacts on Sustainable Logistic Performance - Fernando, Yudi; Chat, Chukai (Elsevier, 2018)
This paper investigates value co-creation and the impact of GST on sustainable logistic performance (SLP). Prior to data collection, metrics were verified utilizing pre-and pilot tests to ensure that measurement items were properly adapted. Then, an e-survey was conducted among Goods and Service Tax (GST) registered logistic service providers (LSPs) in Malaysia using stratified random sampling. A total of 145 LSPs registered under the Malaysian GST scheme participated in the survey. The study found that open dialogue and limited access during value co-creation partially supported SLP. A positive link proved that risk assessment and transparency fully supported SLP. LSPs that have not conquered the nuisances of GST implementation have a reduced ability to compete globally. LSPs are needed to create useful CSR programmes and civilian-led humanitarian operations when a natural disaster occurs. The LSPs that have a high degree of SLP can create more job opportunities for disabled workers, provide a better workplace for women employees and increase employment for ethnic minorities.